PATTERN OF SEVERITY ON THE BASIS OF ELECRODIAGONOSTIC STUDIES IN PATIENTS WITH CARPAL TUNNEL SYNDROME: Carpal Tunnel Syndrome - Akhlaque, Uzma; Waheed, Akhtar; Ali, Liaqat (Pakistan Armed Forces Medical Journal, 2014)
Objective: To study the pattern of severity in patients with Carpal Tunnel Syndrome (CTS) presented at electrodiagnostic clinic at Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi.Study Design: Cross-sectional descriptive study.Place and Duration of the Study: Electro-diagnostic Department of Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi for 6 months from 1st July 2012 to 31st Dec 2012.Subjects and Methods: One hundred and fifty hands from 96 Patients, both male and female were sampled according to inclusion criteria by non-probability purposive sampling. Nerve conduction studies (both motor and sensory studies) were performed using Xeltec electrodiagnostic machine. In patients with normal standard testing but with positive clinical features comparison testing was performed. Results were interpreted and graded according to severity.Results: Out of total 150 hands, 38 hands (25.3%) had minimal CTS, 31 (20.7%) had mild, 56 (37.3%) had moderate, while 21 (14%) had severe CTS. Four (2.7%) patients had extensive lesion. Out of all 96 patients 54 (56.25%) had bilateral disease and rest 42 (43.75%) had unilateral disease.Conclusion: The study showed that the most frequent grade at the time of presentation to electro diagnostic clinic is “moderate” followed by minimal. Since in a large fraction of symptomatic population standard tests were normal, comparison testing is important for early diagnosis.